Immunohistochemical Study of Expression of Cyclynd1 Expression in Invasive and Non-invasive Odontogenic Cysts - Najmeh Jafari; Seyed Hosein Tabatabaei; Raheleh Karimi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: A radicular cyst is an inflammatory cyst arising from the remnants of epithelial malassez, while the Dentigerus cyst is linked to the impacted crown. The odontogenic Keratocyst is a developmental cyst that exhibits suggesting invasive behavior and a propensity to adjacent tissues, potentially due to the proliferation of the epithelial lining or the enzymatic composition of the cyst wall. CyclynD1 is a protein in the Rb pathway that regulates the shift from G1 to S phase. This protein can enable the cell to bypass cell cycle checkpoints and is crucial in lesion development. Considering the varied outcomes and limited research on the expression of the aforementioned marker in odontogenic cysts ، the aim of this study was to compare odontogenic keratocysts (OKC) with two types of non-invasive inflammatory and growth-developmental cysts. Methods: Following a review of the patient records from the Pathology Department of Dental School of Yazd for all jaw cysts، 15 blocks from each of the three cyst types with adequate tissue were chosen for immunohistochemical staining using the Cyclin D1 marker. The stained cell count under a light microscope at x400 magnification was performed and the findings were analyzed using SPSS16 software utilizing Mann-Whitney and Kruskal-Wallis tests. Results: There was no statistically significant difference observed among the three cysts regarding epithelial coverage (p = 0.226) and connective tissue (P = 0.578). Conclusion: Based on the findings of this study، the high expression of this marker in odontogenic Keratocyst may signify its involvement in the pathogenesis and progression of this cyst in contrast to other cysts.